2021
DOI: 10.2478/hukin-2021-0053
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Crank Resistance on Arm Configuration and Muscle Activation Variances in Arm Cycling Movements

Abstract: Arm cycling on an ergometer is common in sports training and rehabilitation protocols. The hand movement is constrained along a circular path, and the user is working against a resistance, maintaining a cadence. Even if the desired hand trajectory is given, there is the flexibility to choose patterns of joint coordination and muscle activation, given the kinematic redundancy of the upper limb. With changing external load, motor noise and changing joint stiffness may affect the pose of the arm even though the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…The neurophysiological and biomechanical responses of arm-cycling have been of interest in recent years due to its affect on performance improvement and injury prevention (Kraaijenbrink et al, 2021). During arm-cycling, variations such as forearm position (Lockyer et al, 2021a), cycling direction (Lockyer et al, 2021a;Nippard et al, 2020), intensity (Chaytor et al, 2020;Forman et al, 2016;Mravcsik et al, 2021), and work volume (Mravcsik et al, 2021) have been shown to modulate corticospinal excitability which may impact the power output, crank-pedal force production and neuromuscular activity (Chaytor et al, 2020;Lockyer et al, 2023). To the best of our knowledge, no comparison has been performed on arm-cycling with regards to forearm position and their influence on power output, crank-pedal forces and bilateral muscle activity.…”
Section: Introductionmentioning
confidence: 99%
“…The neurophysiological and biomechanical responses of arm-cycling have been of interest in recent years due to its affect on performance improvement and injury prevention (Kraaijenbrink et al, 2021). During arm-cycling, variations such as forearm position (Lockyer et al, 2021a), cycling direction (Lockyer et al, 2021a;Nippard et al, 2020), intensity (Chaytor et al, 2020;Forman et al, 2016;Mravcsik et al, 2021), and work volume (Mravcsik et al, 2021) have been shown to modulate corticospinal excitability which may impact the power output, crank-pedal force production and neuromuscular activity (Chaytor et al, 2020;Lockyer et al, 2023). To the best of our knowledge, no comparison has been performed on arm-cycling with regards to forearm position and their influence on power output, crank-pedal forces and bilateral muscle activity.…”
Section: Introductionmentioning
confidence: 99%